SUCCESSFUL MANAGEMENT OF TRISMUS IN A RARE CASE OF FIBROUS DYSPLASIA OF THE CORONOID PROCESS - Dr. Khushboo Walecha*, Dr. Vipul Nanda, Dr. Pawan Goyal, Dr. Manik Sharma, Dr. Avinash Agarwal (Innovative Journal of Medical and Health Sciences, 2020)
Fibrous dysplasia (FD) is a slowly progressive benign bone condition in which normal bone is replaced by an abnormal fibro-osseous tissue. FD has various manifestations and can present with significant cosmetic and functional disturbances, particularly in the craniofacial skeleton. We present a craniofacial fibrous dysplasia (CFD) case in a 6 year old child who presented with severely reduced mouth opening and some aesthetic concerns. The patient underwent left side coronoidectomy and contouring of the involved facial skeleton through bicoronal approach. There was significant improvement in mouth opening. The patient was very satisfied with the outcome. This case report highlights the importance of individualized treatment plan addressing the patient’s concerns. Key words: Fibrous dysplasia–Craniofacial fibrous dysplasia–McCune-Albright syndrome